Electronic properties and photoactivity of monolayer MoS2/fullerene van der Waals heterostructures. Issue 49 (3rd May 2016) - Luo, Cai-Yun; Huang, Wei-Qing; Xu, Liang; Yang, Yin-Cai; Li, Xiaofan; Hu, Wangyu; Peng, P.; Huang, Gui-Fang
Abstract : van der Waals (vdW) heterostructures have attracted immense interest recently due to their unusual properties and new phenomena. Abstract : van der Waals (vdW) heterostructures have attracted immense interest recently due to their unusual properties and new phenomena. Atomically thin two-dimensional MoS2 heterostructures are particularly exciting for novel photovoltaic applications, because monolayer MoS2 has a band gap in the visible spectral range and exhibit extremely strong light–matter interactions. Herein, first-principles calculations based on density functional theory is used to investigate the effects of vdW interactions on changes in the electronic structure, charge transfer and photoactivity in three typical monolayer MoS2 /fullerene (C60, C26, and C20 ) heterostructures. Compared to monolayer MoS2, the band gap of the heterostructures is smaller, which can enhance the visible light absorption and photoinduced electrons transfer. The amount of charge transfer at interface induced by vdW interaction depends on the size of fullerenes. Most importantly, a type-II, staggered band alignment can be obtained in the MoS2 /C20 heterostructure, leading to significantly reduced charge recombination and thus enhanced photocatalytic activity. These results reveal that fullerene modification would be an effective strategy to improve the photocatalytic performance of semiconductor photocatalysts.